Supporting Local Actors in Times of Conflict: The Civil Peace Service and Its Various Actors - Ruppel, Samantha; Rieche, Bernd; Sayndee, T. Debey; Schlimpert, Christoph; López, María Requena; Pastoors, Daniela (In Factis Pax: Journal of Peace Education and Social Justice, 2023)
In the last years, the number of articles that have been calling for a stronger influence of local actors in conflict transformation and peacebuilding has been steadily increasing. At the practical level of peace-work, we can already find some examples where the local actors play an important role in the peace processes. This cooperative work can be found for example in the German Civil Peace Service (CPS) that is working in (post-) conflict countries with the aim of involving and working together with local actors in local peace processes. This article reflects on this cooperation and looks into the following questions: How can partnership in peacebuilding look like? What role do power-asymmetries play in the work of the CPS? And what do people working in the area of CPS need and what do they do? To answer these questions, the article uses the unique method of storytelling in order to combine voices from CPS-actors as well as researchers in order to discuss different perspectives and answers to this question. The article will introduce the CPS, its history, and forms of cooperation, will speak about chances and limitations for both local actors as well as German peace workers during the cooperation but also in their training and accompaniment and will close with recommendations for peace work that aims to cooperate with local actors.